Tax Potency On Peer To Peer Lending Business - Aribowo, Irwan; Kuntonegoro, Hariomurti Tri; Rofi’ah, Laily; Suryono, Agus; Muluk, Khairul; Wijaya, Andy Fefta (WIM Solusi Prima, 2022)
In 2019, the transaction value of digital economy has reached 40 billion with a projected growth of 49% per year. One of the fast growing digital economy in Indonesia is Peer to Peer Lending (P2P Lending) fintech. The Directorate General of Taxes (DGT) as tax authority must be careful in taking the advantage of opportunities to optimize tax revenue. This study describes the exploration of tax potency in P2P lending business carried out by tax officers. The focus of this research is to find out the taxation aspects of the P2P lending business, to find out how to extract potencies carried out by the tax authorities, and to find out the obstacles in extracting tax potency in the field. The analysis used in this study is qualitative methods. The results indicate that extracting tax potency in this business is still not optimal. Factors that become obstacles in exploring the potency are the limited access to financial data of taxpayers, the absence of specific tax rules regulating the P2P lending business, and the lack of cooperation between interrelated agencies.